A Comparison of Cement and Guar Gum Stabilisation of Oxford Clay Under Controlled Wetting and Drying Cycles - Kanishka Sauis Turrakheil; Syed Samran Ali Shah; Muhammad Naveed (Applied Sciences, 2025)
Climate-induced wetting and drying (WD) cycles significantly affect the long-term performance of geotechnical structures. This study explores expansive Oxford clay’s mechanical and volumetric responses stabilised with ordinary Portland cement (OPC) and guar gum (GG) under repeated WD cycles. We prepared 108 samples in total—36 untreated, 36 treated with OPC, and 36 treated with GG. These samples were compacted to 90% of their maximum dry density and subjected to 1, 5, 10, and 15 WD cycles, with nine samples for each treatment at each cycle. During the WD cycles, we monitored volumetric strain and moisture content. Mechanical performance was assessed through unconsolidated undrained triaxial tests conducted at matric suctions of −1500 kPa, −33 kPa, and under saturated conditions. We evaluated the undrained shear strength (Su), secant modulus of elasticity (E50), and modulus of toughness (Ut). The results showed that OPC-treated samples consistently exhibited the highest Su at −1500 kPa across all WD cycles, followed by untreated and GG-treated samples. At −33 kPa, OPC-treated samples again outperformed the others in Su, while GG-treated samples performed better than the untreated ones. Under saturated conditions, GG-treated samples displayed a similar Su to OPC-treated samples, significantly higher than untreated samples. Energy absorption capacity, measured through Ut, peaked for OPC-treated samples at −1500 kPa but favoured GG treatment at −33 kPa and under saturation. X-ray computed tomography (CT) revealed severe degradation in untreated samples, characterised by extensive cracking, minor cracking in OPC-treated samples, and minimal damage in GG-treated samples. This highlights the superior resilience of guar gum to wetting–drying cycles. These findings underscore the potential of guar gum as a sustainable alternative to cement for enhancing the WD resilience of expansive soils, particularly under low-suction or saturated conditions.